Readiness to Exhibit Organizational Citizenship Behaviour among Local Government Employees: A Demographic Analysis - Ibrahim, Rashidah Mohamad; Abu Bakar, Nor Mazlina; Amin, Aziz (Sekolah Tinggi Ilmu Ekonomi Riau, 2019)
Local government, being the manager of urban environment, ranked last under the Malaysia government structure after Federal and State governments. The main function of local government is to stimulate economic growth and social development of a district. However, the operational roles that these local governments supposed to portray have to some extent do not meet the public expectations, resulting in various complaints being filed through various channels as compiled by Public Complaint Bureau. In response to the public outcry for better service delivery, the objectives of this research are to investigate the effect of demographic factors namely (i) gender, (ii) age, (iii) working experience, (iv) supervision tenure and (v) service group in influencing the exhibition of citizenship behavior among local government workforce in east coast region of Malaysia. 126 respondents from three local governments working in east coast states of Malaysia have participated where data were collected using stratified random sampling approach. Empirical results revealed that only supervision tenure has significant influence in elevating employees’ Organizational Citizenship Behavior, hence, supporting social exchange theory. Therefore, management should undertake hands-on actions in warranting that these demographic variables be strengthened in invoking employees’ citizenship behavior towards instilling public confidence towards multifarious services provided by local governments